Students’ and Lecturers’ Needs in the Design of the NanoPintar E-Module for Cell Biology Courses through Multiple Intelligences - Susanti, Diana; Desa, Shakinaz (Balai Publikasi Indonesia, 2026)
Cell Biology is a crucial yet challenging subject in which students often struggle with abstract concepts, particularly cell organelles, a difficulty exacerbated by traditional teaching methods that utilize static materials, which yield inadequate results, especially among students with limited visual-spatial abilities. This research investigated the preliminary needs of both students and lecturers for the development of the NanoPintar e-module using diverse data collection methods, including questionnaires, interviews, student visualization tests, and multiple intelligence assessments. The results indicated very low scores in student visualization and multiple intelligence tests; however, interview and questionnaire outcomes strongly confirmed that both students and lecturers require a NanoPintar e-module for the Cell Biology course, identifying the Endoplasmic Reticulum material as the most difficult topic and thus highly suitable for the development of the e-module